Infrarenal and pararenal abdominal aortic aneurisms: results of open surgical repairmen - Talledo, Oscar (2021)
Objective: To To determine the clinical outcomes of patients undergoing open surgical repairmen of abdominal aortic aneurisms (AAA), infrarenal abdominal aortic aneurisms (IAA) and pararenal abdominal aortic aneurisms (PAA). Methods: A case series involving the review of 75 patient records with AAA, 55 with IAA and 20 with PAA over a period of 5 years. Results: No intraoperatory mortality was detected in the 56 cases of elective surgeries for AAA, IAA and PAA. In cases of rupture AAA, the intraoperatory mortality was 31.6% (3/10 IAA and 3/9 PAA). Transient renal dysfunction KDIGO stage I in 14% of IAA and 33% of PAA. There was a need for re interventions in 9% all of them successful (4% early and 5% late). Conclusions: Elective open surgical repairmen of AAA, IAA and PAA can be performed at low intraoperatory risk for both morbidity and need for re intervention. In patients with rupture AAA, shock was associated with intraoperatory mortality. These results are similar to those reported from foreign specialized centers.